2021
DOI: 10.1080/20008198.2021.2001190
|View full text |Cite
|
Sign up to set email alerts
|

Complex post-traumatic stress disorder and post-migration living difficulties in traumatised refugees and asylum seekers: the role of language acquisition and barriers

Abstract: Background Numerous traumatic experiences and post-migration living difficulties (PMLDs) increase the risk of developing symptoms of complex post-traumatic stress disorder (CPTSD) among Afghan refugees and asylum seekers, living in Austria. Research has repeatedly associated higher levels of CPTSD with higher levels of PMLDs. Summarizing PMLDs into empirically derived factors might facilitate a further understanding of their interaction with symptom presentation within distinct clusters of CPTSD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…More specifically, Frost (58) reported an experience of being an unarmed civilian during war/revolution/military coup and experiencing a serious accident as predictors of PTSD class membership. Accordingly, cPTSD was also associated with a higher number of traumatic events (58,59,70,71) and there was an association with childhood trauma: Younger age at first trauma predicted cPTSD symptoms in treatment-seeking refugees in Niger (60), membership in the cPTSD cluster was associated with a higher total number of childhood traumatic event types in treatment-seeking Afghan refugees (72), and more childhood adversities were found for refugees with cPTSD than for those with PTSDICD-11 in West Papuan refugees (59,70). Frost et al (58) found that physical assault, neglect, sexual assault, and serious accident were predictors of cPTSD class membership in a refugee subsample from a representative sample in the United States.…”
Section: Factors Associated With Ptsd and Cptsdmentioning
confidence: 93%
See 2 more Smart Citations
“…More specifically, Frost (58) reported an experience of being an unarmed civilian during war/revolution/military coup and experiencing a serious accident as predictors of PTSD class membership. Accordingly, cPTSD was also associated with a higher number of traumatic events (58,59,70,71) and there was an association with childhood trauma: Younger age at first trauma predicted cPTSD symptoms in treatment-seeking refugees in Niger (60), membership in the cPTSD cluster was associated with a higher total number of childhood traumatic event types in treatment-seeking Afghan refugees (72), and more childhood adversities were found for refugees with cPTSD than for those with PTSDICD-11 in West Papuan refugees (59,70). Frost et al (58) found that physical assault, neglect, sexual assault, and serious accident were predictors of cPTSD class membership in a refugee subsample from a representative sample in the United States.…”
Section: Factors Associated With Ptsd and Cptsdmentioning
confidence: 93%
“…Frost et al (58) found that physical assault, neglect, sexual assault, and serious accident were predictors of cPTSD class membership in a refugee subsample from a representative sample in the United States. Three studies (60,61,64) found no association with the number of experienced traumas, and seven studies (62,63,(66)(67)(68)71,72) found no associations with trauma types, including being a victim of trafficking (63), adverse childhood experiences (68), and experience of torture above and beyond trauma load (67).…”
Section: Factors Associated With Ptsd and Cptsdmentioning
confidence: 95%
See 1 more Smart Citation
“…For this study, a mean score of stressors was calculated, with higher scores representing stressors being a more serious problem. This scale has been widely used to measure ongoing stressors in refugees and has strong psychometric properties (e.g., Schiess‐Jokanovic et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Deeper investigations of this relationship point out that while potentially traumatic experiences were related with posttraumatic stress disorder (PTSD), total distress due to PMLDs showed an relationship with disturbances of self-organisation (DSO) [ 20 ]. An analysis of the associations of various PMLD factors with CPTSD suggested that while language acquisition & barriers predicted the membership to the CPTSD subgroup, the other PMLD factors were equally present in both investigated subgroups [ 21 ]. These findings suggest individual boundaries between the symptom clusters of CPTSD and different forms of PMLDs.…”
Section: Introductionmentioning
confidence: 99%